(untitled) (World Bulletin of Public Health, 2023)
In the Recommendations of the European Society of Cardiology and the European Society for the Study of Diabetes 2007 it is emphasized that the use of angiotensin converting enzyme inhibitors (ACE inhibitors) and adrenoblockers (BAB) is the basis for the treatment of chronic heart failure (CHF) in patients with diabetes mellitus (DM). For the first time, doctors’ attention is drawn to the fact that the appointment of ACE inhibitors to DM patients receiving hypoglycemic therapy may increase the risk of hypoglycemic conditions. Attention to this side of the action of ACE inhibitors is due to the fact that hypoglycemia is an independent risk factor for cardiovascular mortality. The above Recommendations emphasize the urgent need for careful monitoring of the level of glycemia when prescribing ACE inhibitors to patients with diabetes. This is especially necessary in the initial period of combined cardiac and hypoglycemic therapy. The risk of hypoglycemia depends on many factors and, apparently, varies in different contingents of patients with diabetes. According to available data, patients with CHF have an increased tendency to hypoglycemia due to a decrease in the body’s tolerance to a decrease in blood glucose levels. Such functional insufficiency is largely determined by a violation of the processes of gluconeogenesis in the liver and the secretion of glucagon by the pancreas, which are normally included in the body’s defense system against a pronounced decrease in blood glucose